RDA and serials cataloging - Jones, Ed. (Chicago : ALA Editions, an imprint of the American Library Association, 2013)
Serials and continuing resources present a variety of unique challenges in bibliographic management, from special issues and unnumbered supplements to recording the changes that a long-running periodical can experience over time. Easing catalogers through the RDA: Resource Description and Access transition by showing the continuity with past practice, serials cataloging expert Jones frames the practice within the structure of the FRBR and FRAD conceptual models on which RDA is based. With serials' special considerations in mind, he Explains the familiarities and differences between AACR2 and RDA Demonstrates how serials catalogers' work fits in the cooperative context of OCLC, CONSER and NACO Presents examples of how RDA records can ultimately engage with the Semantic Web Occasional serials catalogers and specialists alike will find useful advice here as they explore the structure of the new cataloging framework.
Includes bibliographical references and index.
rpm 24/10/2017
Loans
Keywords: Cataloging of serial publications; Cataloging of integrating resources; Resource description & access